Parental Investments and Socio-Economic Gradients in Learning across European Countries - Pedro Carneiro; Hugo Reis; Alessandro Toppeta (Institute of Labor Economics (IZA), 2024)
Generous maternity leave, affordable daycare, extensive social safety nets, excellent universal health care, and high-quality public schools, are all notable features of Nordic countries. There is a widespread belief that such strong public investments in children contribute to a levelled playing field and promote social mobility. However, gaps in learning outcomes between children of rich and poor parents remain as high in Nordic countries as elsewhere in Europe. One explanation for this paradox is that the equalizing impacts of public investments are undone by parental investments in children of rich and poor families, which are as unequal in Nordic countries as in the rest of the European continent.
Keywords: J62; D63; I21; J24; 330; intergenerational transmission; inequality; education; human capital